Diversity of mucins in labial glands of infants - Stoeckelhuber, Mechthild; Kesting, Marco Rainer; Loeffelbein, Denys J.; Schmitz, Christoph; Wolff, Klaus-Dietrich (Histology and Histopathology, 2020)
Mucins as highly glycosylated proteins comprise multiple functions like protection, homeostasis, immune defense, cell signaling. Various epithelial tissues including glandular structures express different specific mucin types. We investigated labial salivary glands in infants for the occurrence of MUC1, MUC2, MUC3, MUC4, MUC5AC, MUC5B, and MUC7 by immunohistochemistry. MUC1 and MUC4 were detected in serous and ductal glandular cells, partially intensified at the apical plasma membrane. MUC3 was found in ductal glandular cells and in myoepithelial cells. MUC5B exhibited a mosaic expression pattern in mucous glandular endpieces. MUC2 and MUC7 were abundant in serous acini. Glandular structures were negative for MUC5AC. A comprehensive study of specific mucins in labial salivary glands of infants was presented for the first time. As a representative of the minor salivary glands, labial glands are, due to their localization, directly exposed to environmental influences. The distribution of a broad spectrum of mucins in infantile labial glands indicates their importance early in human development to sustain oral health.
CRIS-Team WoS Importer:2020-08-28